Early Childhood Writing Readiness Influencing Factors and the Roles of Teachers and Parents - Widiyanti, Dita; Anggreni, Anggreni (Jurnal Penelitian Medan Agama, 2025)
This study aims to improve the writing readiness of children aged 5-6 years through educational games at RA Al-Fattah Sidotani I, Bandar District, Simalungun Regency. Writing readiness is an important aspect in the development of early childhood which includes fine motor skills, hand-eye coordination, and interest in writing activities. The method used in this study is Classroom Action Research (CAR) which is carried out in two cycles, with stages of planning, action implementation, observation, and reflection. Data collection techniques are carried out through observation, documentation, and assessment of children's performance. The results of the study showed that through the implementation of educational games such as tracing shapes, connecting dots, and arranging letters, there was a significant increase in children's writing readiness, with pre-test results of 33%, cycle I 56% and cycle II 83% which showed that children became more skilled in using writing tools, showed increased fine motor coordination, and were more enthusiastic and confident in participating in writing activities. Thus, educational games have proven to be effective as a learning strategy that is in accordance with the characteristics of early childhood. This study recommends that PAUD teachers systematically integrate educational games into learning activities to support children's academic readiness, especially in writing skills.